Comparative capitalism aproaches to corporate social responsibility: how institutions and practices co-evolve? - Soares, Rômulo Alves (2021)
This research seeks to deepen the understanding of how the institutional environment can affect corporate social responsibility (CSR) practices. In order to do this, the thesis was elaborated in three papers that seek to fill gaps observed in the literature that concerns the relationship between the institutional environment and CSR. In the first paper, we investigate how pressure from stakeholders and the motivations for adopting CSR practices affect the way in which domestic and foreign companies operating in Brazil engage in the adoption of such practices. We used survey data for 140 companies in five industries (food, toys, electronics, personal care and hygiene, and textiles). The research shows the existence of two clusters of companies operating in Brazil. The first cluster is composed of companies that actively engage in CSR practices, since they perceive greater financial or reputational benefits from their adoption, as well as perceive greater pressure from stakeholders. The second cluster is made up of companies with less engagement in CSR practices, prioritizing mandatory and employeeoriented practices. Such companies perceive less financial and reputational benefits from the adoption of CSR practices, in addition to perceived pressure from a smaller range of stakeholders. In general, the result of the first paper shows that there is room for different responses in the Brazilian context, which is in contrast to what is observed in the literature. The second paper of the thesis expands the scope of the first by assessing CSR disclosure practices of 86 companies in eight countries. The paper shows that the disclosure of CSR of companies in liberal and coordinated economies, has its behavior coherently described by the Varieties of Capitalism. However, companies in developing countries, such as Brazil and India, have not shown the same adequacy, which shows the need to seek new theoretical approaches to explain CSR practices in these countries. In this sense, the third paper of the thesis, using a sample of 253 companies, from five countries, aims to investigate, from the perspective of the Variety of Institutional Systems, how the adoption of different CSR practices is going through a dynamic process, which unfolds differently in developed and developing countries.